INHIBITORY ACTIVITY OF ALLIUM SATIVUM L. EXTRACT AGAINST STREPTOCOCCUS PYOGENES AND PSEUDOMONAS AERUGINOSA - Savitri, Natasha Hana; Indiastuti, Danti Nur; Wahyunitasari, Manik Retno (Journal of Vocational Health Studies, 2019)
Background: One of the most common health problems is infectious diseases. Infectious disease can be caused by bacteria. There were two groups of bacteria based on the staining, Gram-positive and Gram-negative bacteria. Purpose: Antibiotics are the main therapy used in the incidence of bacterial infections. But over time, some antibiotics became resistance. Several studies have shown that garlic has an antibacterial effect. The content of allicin, ajoene, saponins, and flavonoids is found in garlic which has antibacterial properties. The antibiotic activity test of garlic was carried out on the bacteria Streptococcus pyogenes and Pseudomonas aeruginosa. The goal of this study is to investigate the antibacterial effect of Allium sativum L. extract against Streptococcus pyogenes and Pseudomonas aeruginosa. Method: Garlic extract was made using the maceration method using 96% alcohol as the solvent. Tube dilution method elected to observe garlic antibiotic activity. This test aims to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). There were eight different concentration used, i.e. 2 grams/ml, 1 gram/ml, 0.5 gram/ml, 0.25 gram/ml, 0.125 gram/ml, 0.0625 gram/ml, 0.03125 gram/ml, and 0.015625 gram/ml. Replication is done three times. Result: In this experiment, the extract produced was turbid that MIC could not be determined and there was no momentous differentiation between before and after treatment. There was no growth of Streptococcus pyogenes in 1 gram/ml and Pseudomonas aeruginosa in 0.5 gram/ml. This number indicates the MBC for each bacteria. Conclusion: Garlic (Allium sativum L.) has an effect of bactericidal activity, it can perform as an antibacterial for Streptococcus pyogenes and Pseudomonas aeruginosa. Garlic extract was more effective for Pseudomonas aeruginosa than Streptococcus pyogenes.